Mapping the pathways between recreational cannabis use and mood disorders: A Behaviour Sequence Analysis approach. (19th June 2019) - Keatley, David A.; Walters, Isobel; Parke, Adrian; Joyce, Tara; D. Clarke, David
Abstract: Issues Addressed: Although cannabis use is still illegal in most places around the world, it remains a widely used drug. The recreational use of cannabis has been linked to multiple mental wellbeing issues, including psychosis, depression and anxiety. The objective of this study was to investigate the temporal dynamics of cannabis use in relation to mental health issues. Methods: The current research uses a novel methodological approach, behaviour sequence analysis, to understand the temporal relationship between recreational cannabis use and surrounding issues related to mental wellbeing, in a sample of 61 participants who had written autobiographical accounts online. Results: The results indicated a bi‐directional temporal ordering between cannabis use and mood disorders. Cannabis use preceded psychosis and can also exacerbate symptoms of psychosis, depression and anxiety. Findings also suggested that low self‐esteem may be a predictor of future cannabis use. Conclusions: Research shows a link between mood disorders and recreational cannabis use. The BSA method can be used in applied settings to map pathways in individuals' life histories. So what?: The current study shows the sequential links between cannabis use and psychosis, depression and anxiety. Results show there is no single clear pathway and clinical practitioners should focus on a wider range of factors in individual's case histories.